2010
DOI: 10.1523/jneurosci.4816-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Excites Proopiomelanocortin Neurons via Activation of TRPC Channels

Abstract: Leptin can exert its potent appetite-suppressing effects via activation of hypothalamic proopiomelanocortin (POMC) neurons. It depolarizes POMC neurons via activation of a yet unidentified nonselective cation current. Therefore, we sought to identify the conductance activated by leptin using whole-cell recording in EGFP-POMC neurons from transgenic mice. The TRPC channel blockers SKF96365 (1-[␤-[3-(4-methoxyphenyl)propoxy]-4-methoxyphenethyl]-1H-imidazole hydrochloride), flufenamic acid, and 2-APB (2-aminoethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
255
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(277 citation statements)
references
References 28 publications
21
255
0
1
Order By: Relevance
“…The LV component proved sensitive to 2-APB, a blocker of TRPC1, TRPC3, TRPC4, TRPC5, and TRPC6 channels, yet insensitive to SKF96365, a blocker of TRPC6 and TRPC7 channels (Clapham et al, 2005). This pharmacological profile is similar to that reported for the cholecystokinin-activated MCC in rat amygdala interneurons (Chung and Moore, 2009) but distinct from that reported for leptin responses in Arc POMC neurons, effects mediated via the activation of another member of the class I cytokine receptor family, Ob-Rb (Qiu et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The LV component proved sensitive to 2-APB, a blocker of TRPC1, TRPC3, TRPC4, TRPC5, and TRPC6 channels, yet insensitive to SKF96365, a blocker of TRPC6 and TRPC7 channels (Clapham et al, 2005). This pharmacological profile is similar to that reported for the cholecystokinin-activated MCC in rat amygdala interneurons (Chung and Moore, 2009) but distinct from that reported for leptin responses in Arc POMC neurons, effects mediated via the activation of another member of the class I cytokine receptor family, Ob-Rb (Qiu et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…3C), in which an LV and a HV component could be identified. The inward current responsible for depolarization-the LV component-exhibits a negative slope conductance (approximately Ϫ50 mV) and is attenuated in Na ϩ -substituted aCSF and augmented in low-Ca 2ϩ /high-Mg 2ϩ aCSF (Qiu et al, 2010). This suggests a Na ϩ -dominated MCC mediated through TRPC channels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…69 Leptin is also considered a proinflammatory adipokine because of the actions it exerts in several cells of the immune system, including monocytes/macrophages, dendritic cells, neutrophils, eosinophils, basophils, natural killer cells, and lymphocytes. [70][71][72][73] Qiu et al 74 suggested that a Janus 2 tyrosine kinase (Jak 2)-dependent pathway via stimulation of PI3 kinase and PLCgamma1 activated TRPC channels. Therefore, we think that leptin through a Jak2-PI3 kinase-PLCgamma pathway may activate TRPC4b channels in INS-1 cells.…”
Section: The Roles Of Glucocorticoids and Leptin Via Trpc4 In Insulinmentioning
confidence: 99%